Animal Acts Performing Species Today - Hughes, Holly; Chaudhuri, Una (University of Michigan Press, 2018)
We all have an animal story-the pet we loved, the wild animal that captured our childhood imagination, the deer the neighbor hit while driving. While scientific breakthroughs in animal cognition, the effects of global climate change and dwindling animal habitats, and the exploding interdisciplinary field of animal studies have complicated things, such stories remain a part of how we tell the story of being human. Animal Acts collects eleven exciting, provocative, and moving stories by solo performers, accompanied by commentary that places the works in a broader context. Work by leading theater artists Holly Hughes, Rachel Rosenthal, Deke Weaver, Carmelita Tropicana, and others joins commentary by major scholars including Donna Haraway, Jane Desmond, Jill Dolan, and Nigel Rothfels. Una Chaudhuri's introduction provides a vital foundation for understanding and appreciating the intersection of animal studies and performance. The anthology foregrounds questions of race, gender, sexuality, class, nation, and other issues central to the human project within the discourse of the "post human," and will appeal to readers interested in solo performance, animal studies, gender studies, performance studies, and environmental studies.